Comparing the effect of FUAS and myomectomy on the elasticity of myometrium around targeted uterine fibroid - Ziyao Wang; Yan Ma; Jia Zhou; Feng Jiang; Jin-yun Chen; Wen-zhi Chen (International Journal of Hyperthermia, 2024)
Background Focused ultrasound ablation surgery (FUAS) has been widely employed to treat patients with uterine fibroid (UF). This study aimed to estimate myometrial stiffness changes in patients who received FUAS for UFs or myomectomy (ME) and compare the recovery of surrounding myometrium between FUAS and ME groups. Our results may provide more evidence for guiding the proper conception timing in patients with UF.Methods This study enrolled 173 patients from May 2022 to August 2023. Shear wave elastography (SWE) was used to dynamically monitor myometrial elasticity changes in patients before and after surgery. Moreover, our study monitored and analyzed the stiffness changes in the targeted fibroid after FUAS, as well as in the myometrium around after FUAS or ME.Results The stiffness of the myometrium around the resected fibroid was significantly higher than at the preoperative level until 6 months. Conversely, the stiffness of the surrounding myometrium was only temporarily increased 1 day after FUAS. The comparison between FUAS and ME groups regarding the stiffness of the surrounding myometrium showed that nonsignificant differences were detected between the two groups before the treatment. The stiffness of the surrounding myometrium in the ME group was statistically significantly higher than that of the FUAS group 1 day as well as 1, 3, and 6 months after the treatment, respectively.Conclusion The FUAS had less impact on the surrounding myometrium than the ME, which may be more conducive to the recovery of myometrial elasticity in patients with UF.